2008
DOI: 10.1002/jssc.200800292
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of metal–EDTA complexes by flow injection analysis with electrospray ionization mass spectrometry and ion chromatography with inductively coupled plasma mass spectrometry

Abstract: Original PaperSpeciation of metal-EDTA complexes by flow injection analysis with electrospray ionization mass spectrometry and ion chromatography with inductively coupled plasma mass spectrometry Flow injection analysis (FIA) with ESI-MS and ion chromatography (IC) with inductively coupled plasma-MS (ICP-MS) and their MS spectral showed that these metal -EDTA complexes were present in solution. Based on the ESI-MS, ion chromatographic separation and ICP-MS detection of these complexes are possible because IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 38 publications
2
36
0
1
Order By: Relevance
“…Overall, our findings agreed well with those from other studies and the predictions from the speciation models: Most EDTA-compounds described by previous reports including uncomplexed EDTA and metal-EDTA were detected in this study as well as predicted by the PHREEQC calculations ( Table 3, Chen et al, 2008;Reinoso-Maset et al, 2012). In addition, mostly monomers, and only two dimers were detected, indicating that metal-EDTA equilibrium studies are likely to be comparable amongst different experimental and instrumental setups.…”
Section: Metal-ligand Speciation Patterns: Integrity and Reproducibilitysupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, our findings agreed well with those from other studies and the predictions from the speciation models: Most EDTA-compounds described by previous reports including uncomplexed EDTA and metal-EDTA were detected in this study as well as predicted by the PHREEQC calculations ( Table 3, Chen et al, 2008;Reinoso-Maset et al, 2012). In addition, mostly monomers, and only two dimers were detected, indicating that metal-EDTA equilibrium studies are likely to be comparable amongst different experimental and instrumental setups.…”
Section: Metal-ligand Speciation Patterns: Integrity and Reproducibilitysupporting
confidence: 92%
“…Both Cu(I) and Cu(II) were involved in the 1:1 complex formation with SA, while Fe was bound as Fe(III) ( Table 5). Chen et al (2008) and # described by Reinoso-Maset et al (2012). …”
Section: Speciation Patterns Of the Target Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 showed the amplified view of the MS spectral region between m/z 490 and 500. The intensity ratio of peaks at m/z 497, 496, and 495 was 1:0.49:0.60, which approximately agreed with the lead natural isotopic ratio (1:0.42:0.46) although our experimental values were higher than the theoretical estimate [61]. In addition, we found that the peak at m/z 493 was not very stable especially when analyzing complex samples, and an example of a high peak collected in our experiments was shown in Fig.…”
Section: Qualitative Characterizationsupporting
confidence: 83%
“…Although further studies are necessary, one of the possible reasons for the isotopic ratio difference is that EESI has a different ionization mechanism than that of ESI. The isotopic ratio in this study was measured in the liquid phase by EESI where solvent-dependent extractive process plays an important role [59], while the previous study was conducted by ESI in the gas phase [61]. The peak at m/z 497 was tentatively assigned to [EDTAþ 208 Pb-3H] À .…”
Section: Qualitative Characterizationmentioning
confidence: 98%